Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.12659/msm.898616
|View full text |Cite
|
Sign up to set email alerts
|

P53 and Murine Double Mimute 2 (MDM2) Expression Changes and Significance in Different Types of Endometrial Lesions

Abstract: BackgroundEndometrial lesions are common in obstetrics and gynecology, including endometrial polyps, uterine adenomyosis, and malignant endometrial adenocarcinoma. Endometrial lesions seriously affect women’s health, fertility, quality of life, and life safety. As a pro-apoptosis gene, p53 is considered to be closely related with human tumors. Murine double mimute 2 (MDM2) is an oncogene that can promote tumor occurrence and development. P53 and MDM2 expression and significance in different types of endometria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…The findings in the literature regarding the loss PTEN protein expression and clinical outcome in endometrial carcinomas are inconsistent. Some studies have reported more favorable survival (14,28,29,91,95,96), while other studies have indicated less favorable prognosis (19,90,97,98). Terakawa et al (97) suggested that overexpression of PTEN is a significant prognostic indicator of improved overall survival for patients with advanced endometrial carcinoma who undergo postoperative chemotherapy, as PTEN was able to increase the chemosensitivity of neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings in the literature regarding the loss PTEN protein expression and clinical outcome in endometrial carcinomas are inconsistent. Some studies have reported more favorable survival (14,28,29,91,95,96), while other studies have indicated less favorable prognosis (19,90,97,98). Terakawa et al (97) suggested that overexpression of PTEN is a significant prognostic indicator of improved overall survival for patients with advanced endometrial carcinoma who undergo postoperative chemotherapy, as PTEN was able to increase the chemosensitivity of neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mdm2 also serves an oncogene role independent of p53. Notably, mdm2 overexpression leads to excessive cell proliferation and promotes tumor formation (29). Inactivation of p53 protein provides the neoplastic cells with a higher capacity for division and proliferation, and therefore contributes to malignant change and tumor formation (17,30).…”
Section: Introductionmentioning
confidence: 99%
“…MDM2 is an oncogene that promotes tumour occurrence and development predominantly by inhibiting the p53 tumour suppressor activity (24). Jiang et al (31) found increased MDM2 mRNA and protein levels with increasing EC grade.…”
Section: Discussionmentioning
confidence: 99%
“…El gen P53 es un gen supresor de tumor que juega un papel importante en la apoptosis celular y el gen MDM2 es un oncogen que puede estimular la proliferación celular del endometrio y otros tejidos. Un estudio realizado en China, donde se seleccionaron 71 muestras de diferentes lesiones endometriales de mujeres sometidas a histerectomía (adenocarcinoma, adenomiosis, poliposis y grupo control), y a las cuales se les realizó PCR en tiempo real para detectar la expresión de los genes P53 y MDM2, se encontró que dicha expresión fue significativamente más elevada en el grupo de adenocarcinoma, seguido por el grupo de pólipos y por último por el de adenomiosis, lo cual refleja que la aparición de pólipos endometriales puede promover la aparición y desarrollo del cáncer, y constituir una lesión preneoplásica; sin embargo hasta el momento no se cuenta con evidencia suficiente que permita establecer un protocolo de manejo de los pólipos endometriales para evitar así su malignización (15).…”
Section: Tratamientounclassified